Ruptured abdominal pregnancy at 35 weeks with live child - a case study at Kara university hospital (Togo) - Aboubakari AS; Ajavon DRD; Dossouvi T; Logbo-Akey KE; Dagbé M; Akpadza K (Barpeta Obstetrics and Gynaecological Society, 2019)
Abdominal pregnancy is a rare form of ectopic pregnancy. Advanced forms with live children at birth are exceptional. We report a case of abdominal pregnancy of 35 weeks with live child, referred and after emergency management. Maternal prognosis was good. The newborn, admitted to pediatric intensive care for breathing difficulties, died 8 days after birth.